Projection of net benefits for companies in the dual VET-apprenticeship programme in Nepal - Thomas Bolli; Johanna Kemper; Mahesh Nath Parajuli; Ursula Renold; Binayak Krishna Thapa (ETH Zurich, KOF Swiss Economic Institute, 2020)
The ENSSURE project entails a component of introducing a Dual VET-Apprenticeship in Nepal. This new formal upper secondary education programme combines about one day of classroom education with about five days of workplace training each week for two years. While this project is in its pilot phase, the question arises whether and how this pilot might represent a first step towards a Dual VET-Apprenticeship system in Nepal. Therefore, this working paper analyses challenges of scaling up the Dual VET-Apprenticeship based on eight semi-structured interviews with experts representing government and industry conducted in May 2019. Hence, this working paper takes a long-term perspective, providing insights regarding potential challenges and implementation barriers to scaling up the programme in the future. The analytical framework distinguishes five dimensions that could be drivers to implementation: commitment, capacity, clients, content and context. Caves and Baumann (2020) differentiate this so-called 5C framework of Najam (1995) into several aspects, allowing to measure implementation drivers and barriers empirically. Figure A1 summarises the results. The results of the expert interviews provide the following insights. Commitment of actors involved in the Dual VET-Apprenticeship is generally high and represents an implementation driver. Capacity in terms of personnel, finances and time also represents an implementation driver. However, capacity in terms of available information represents a potential implementation barrier. The clients dimension captures to what extent actors have the appropriate roles in the programme. Generally, the interview partners assess this as an implementation driver. The content dimension represents the most critically evaluated implementation barrier dimension. Half of the interview partners consider the reform a medium-sized change and half of the respondents even consider it a substantial change. This suggests that the implementation requires substantial adaptations from the involved actors. Furthermore, since the programme involves companies and industry association, the reform requires coordination among more stakeholders than a conventional education reform. This complexity makes scaling up the programme more challenging. Finally, the context dimension is an implementation driver as the interview partners believe that the Dual VET-Apprenticeship fits the Nepali context well.
Keywords: 330; Berufsbildung; Auszubildende; Wirkungsanalyse; Technische Zusammenarbeit; Unternehmen; Nepal